Development of Recombinant Leptospira Antigenes for the Purpose of Creation of Immunoassay Test Kit for Diagnosis of Leptospirosis - V. N. Kulikov; A. A. Kozarenco; N. K. Tokarevich; N. A. Stoyanova (Эпидемиология и вакцинопрофилактика)
Species-specific recombinant proteins of leptospira are genetically engineered by the method of gene manipulation. Their high activity and antigenic specificity are established. On the basis of these proteins an immunoassay test kit for detecting JgG to Leptospira is constructed.